Pelatihan dalam Rangka Mengurangi Perilaku Menyimpang pada Anak Remaja Siswa Sekolah Menengah Atas Swasta Pupuk Iskandar Muda di Lingkungan Kampus Universitas Malikussaleh - Ketaren, Amiruddin; Rangkuty, Rakhmadsyah Putra; Hidayat, Hidayat; Maliati, Nulwita; Nasution, Abdullah Akhyar; Yunanda, Rizki; M. Husen (ASOSIASI IDEBAHASA KEPRI, 2025)
This article describes training on the practice of deviant behavior carried out by senior high school (SMA) students who are in the Malikussaleh University campus environment. The training was conducted at Pupuk Iskandar Muda (PIM) Private High School, Dewantara District, North Aceh Regency. The background of the implementation of this training is the increasingly widespread deviant behavior committed by adolescents, especially high school students, both within the school and outside the school. The school, which was originally expected to be the center of education, has instead become one of the loci of deviant behavior activities itself. Schools through counseling guidance teachers (BK) must work extra hard to deal with the growing situation. This training guides students to behave in accordance with the values and rules that have been agreed upon by all members of society. No longer do actions that violate the rules at school, such as smoking, fighting, insulting and mocking friends, dropping out of school and others even to the point of committing motorcycle robbery, getting involved in drugs and being caught in raids when skipping school. This training also explained about the practice of deviant behavior that can be punished by using special criminal laws for children.